Holocene mean July temperature and winter precipitation in western Norway inferred from palynological and glaciological lake-sediment proxies - Bjune, AE; Bakke, J; Nesje, A; Birks, HJB (ARNOLD, HODDER HEADLINE PLC, 2005)
Reconstructions of mean July temperature (T-jul) and winter precipitation (P-w) for the last 11/500 years on the Folgefonna peninsula are presented. T-jul was reconstructed using pollen-climate transfer functions and P-w was reconstructed based on the exponential relationship between mean solid winter precipitation and ablation-season temperature at the equilibrium-line altitude (ELA) with a reconstructed former ELA, using T-jul as the proxy for ablation-season temperature. The reconstructions from the Folgefonna peninsula suggest that the early Holocene was relatively cool and dry until c. 8000 cal. yr BP, followed by a warm and humid mid-Holocene until c. 4000 cal. yr BP with inferred T-jul above 12 degrees C and P-w reaching as high as 225% of the present day. Subsequent to c. 4000 cal. yr BP a reduction is seen in both inferred T-jul and P-w with large fluctuations during the last 500 years. In addition, new calculations of P-w from two glaciers ( Hardangerjokulen and Jostedalsbreen) in southern Norway are presented. The results show that P-w varied in phase at all glaciers, probably as a response to the same climate forcing factor. During the early Holocene a major shift is suggested between winds from the west and the east.